Causal models for monitoring the progress of infants with low birthweight - Longford,NT; Ramirez,O; Giffe,C; Longford,NT (Revista Brasileira de Biometria -- Brasilian Biometric Journal, 2020)
We study the weight (body mass) of infants born prematurely and with lowbirthweight during the first postnatal year. The infants areenrolled in the Casa Canguroprogramme in Valle de Cauca, a department (province) of Colombia. The current weightand other physiological measurements are recorded at their visits to participating health-care facilities. We compare two groups of infants: those born at 31 weeks of gestationalage or earlier (extremely preterm) and those born at 33 weeks orlater (preterm). Thecomparisons are made using the potential outcomes framework, regarding the two groupsas treatments and selecting from them pairs matched on an extensive set of covariates.Matching is accomplished by propensity scoring. The outcomes (weight and height)at a particular age are approximated by interpolation.We conclude that the averageweight-handicap of the extremely preterm infants first increases, from about 600 gramsat birth to 900 grams on average at three months, and then is reduced, so that by thefirst birthday they are only about 250 grams lighter on average.